HOXA11‐AS regulates JAK‐STAT pathway by miR‐15a‐3p/STAT3 axis to promote the growth and metastasis in liver cancer. Issue 9 (17th May 2019) - Wang, Shasha; Zhang, Shichao; He, Yonggang; Huang, Xiaobing; Hui, Yuanjian; Tang, Yichen
Abstract: Background: HOMEOBOX A11 (HOXA11) antisense RNA (HOXA11‐AS), a newly identified long noncoding RNAs, is involved in the carcinogenic process of several human tumors. However, the role of HOXA11‐AS in liver cancer progression is not well understood. Materials and Methods: This study used liver cancer tissues and cell lines (CSQT‐2 and HCCLM3) to explore the potential mechanism of HOXA11‐AS. Quantitative real‐time polymerase chain reaction and Western blot were applied to evaluate the bio‐molecules expression. Bioinformatics analysis, RNA pull down and luciferase report assay were applied to determine the molecules bind. MTT, transwell, and wound healing assay were used to measure the cell growth situation. Results: HOXA11‐AS was highly expressed in liver cancer tissues and cell lines, which was closely related with poor prognosis in patients with liver cancer. HOXA11‐AS could act as a competing endogenous RNA for miR‐15a‐3p. Besides, miR‐15a‐3p negatively controlled its target molecule signal transducer and activator of transcription 3 (STAT3). Furthermore, a linear regression analysis and biological experiments showed a positive correlation between HOAX11‐AS and STAT3. Moreover, HOAX11‐AS overexpression activated the Janus kinase (JAK)‐STAT pathway and thus promoted the growth, migration, and invasion of liver cancer cells, which might be through regulating miR‐15a‐3p/STAT3 axis. Conclusion: Our study suggested that HOAX11‐AS could regulate the JAK‐STAT signaling pathway by miR‐15a‐3p/STAT3 axis to promote the progression of liver cancer. Thus, HOXA11‐AS may be regarded as an effective biomarker with diagnostic, prognostic, and therapeutic potentials for liver cancer. Abstract : HOMEOBOX A11 antisense RNA (HOXA11‐AS) expression was upregulated in liver cancer tissues and cell lines, which was correlated with poor prognosis in liver cancer patients. HOAX11‐AS could regulate Janus kinase/signal transducer and activator of transcription (STAT) signaling pathway by miR‐15a‐3p/STAT3 axis to promote the progression of liver cancer.